Ownership Structure And Risk Disclosure: The Roles Of Chief Executive Officer (Ceo) Duality And Board Independence In Thailand Companies - Siriwan, Silarak (2023)
This study aims to examine the influence of ownership structure on risk disclosure in the context of Thailand and the effect of CEO duality and board independence on the relationship between ownership structure and risk disclosure from the perspectives of Agency Theory and Signaling Theory.